Compressive Strength and Economic Evaluation of Concrete with Partial Replacement of Coarse Aggregate by Recycled Aggregate - Abdul Awol Rabby; Imon Hasan Bhuiyan; Uzzal Al Aziz; Md Hasan Imam Siddique; Md.Al Amin; Abhijit Nath Abhi (Popular Scientist, 2025)
The depletion of natural aggregates and the rising volume of construction and demolition waste have made sustainable alternatives in concrete production essential. Recycled coarse aggregate (RCA) helps reduce landfill use and reliance on natural resources, but its variable quality raises concerns about structural reliability. Therefore, evaluating the balance between mechanical performance and economic feasibility is crucial for promoting sustainable construction. In this study, concrete mixes were designed with varying RCA replacement levels (0%, 50%, 70%, and 100%) compared to natural coarse aggregate (NCA). A controlled mix proportion of 1:1.5:3 (cement:sand:aggregate) with a water–cement ratio of 0.5 and 1% superplasticizer was employed. To ensure consistency, aggregates were classified into 19 mm (40%), 12.5 mm (30%), and 9.5 mm (30%) gradations. Cylindrical specimens (100 × 200 mm) were cast and cured, followed by compressive strength testing at 7, 14, and 28 days in accordance with ASTM C39. The total material cost for each mix was also computed on a per-cubic-meter basis to assess economic implications alongside strength performance. The results highlight a clear strength–cost trade-off. The control mix (100% NCA) achieved 26.5 MPa at 28 days, while the 50% RCA mix showed only a 3.92% reduction (25.5 MPa) with 18.4% lower cost. At 70% RCA, compressive strength dropped by 10.42% (24 MPa) with a 28.29% cost reduction, whereas 100% RCA replacement resulted in a severe 59.63% strength loss (16.5 MPa) despite maximum cost savings (49.07%). These findings establish 50% RCA + 50% NCA as the most rational compromise, offering structural adequacy with substantial cost efficiency, while also reinforcing RCA’s role in sustainable construction.